The Uganda Muslim supreme council : an experiment in Muslim administrative centralisation and institutionalisation, 1972–82 - Kasozi, Abdu B. K. (Institute of Muslim Minority Affairs. Journal, 1985)
The creation of the Uganda Muslim Supreme Council in 1972 gave Muslims hopes that for the first time their affairs which were formerly administered by a collection of organizations and individuals each in competition with the other, would not only come under one administrative umbrella, but would also promote firm institutional principles and procedures. The first preachers of Islam in these African parts were often traders who propagated the faith in their spare time or as a means to attaining other diplomatic objectives. They did not bequeath administrative institutions to their converts, or prepare them to generate such activity. Nor did they remain in contact with them with the purpose of guiding them in ways of managing Muslim affairs.' As a result, Muslims in sub-Saharan Africa have had no viable administrative institutions national in scope and well organized that are a key to the proper direction of the community